The novel in the ancient world - Schmeling, Gareth L. (Mnemosyne, Supplements, 1996)
This is the second publication in Brill's handbook series The Classical Tradition . The subject of this volume is that group of works of extended prose narrative fiction which bears many similarities to the modern novel and which appeared in the later classical periods in Greece and Rome. The ancient novel has enjoyed renewed popularity in recent years not only among students of literature, but also among those looking for new sources on the popular culture of antiquity and among scholars of religion. The volume surveys the new insights and approaches to the ancient novel which have emerged form the application of a variety of disciplines in the recent years. The 25 senior scholars contributing to the volume are drawn from a broad range of European and North American traditions of scholarship. Chapters cover the important issues dealing with the novel, novelists, novel-like works of fiction, their development, transformation, Christianisation and Nachleben, as well as a broad range of matters, from literary/philological to cultural/historical and religious, which concerns modern scholars in the field. This publication has also been published in paperback, please click here for details.